An Analysis of Biden's Administration Stark Opposite Approaches in Humanitarian Crises - Racharjo, Satrio Imam (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
This paper examines the different approaches of the United States foreign policy towards the Russia-Ukraine and Israel-Palestine conflicts by comparing similar cases in both of the conflicts. The United States, who have been actively criticizing Russia for violating rules-based order and humanitarian values in the Russia-Ukraine conflict, have not done the same to Israel even though there is mounting pressure for similar allegations. The comparisons are analyzed through cases of the United States' aid towards Ukraine and their criticism towards Russia’s international norms violations, Continuing with their military aid to Israel while they are attacking Gaza and staying silent with Israel’s violations. We would also see how international institutions that are supposed to prevent such a crisis are unable to do much to stop the crisis, As well as Israel’s influences in the US foreign policy-making process, which resulted in persistent pro-Israel foreign policies. By analyzing the United States' actions through the concepts of Humanitarian Diplomacy, Hegemon, and Rules-Based International Order, this paper finds that the United States' national interest’s alignment with Ukraine has used humanitarian values and rules-based international order as a political instrument. On the other hand, Israel’s great influence in the United States foreign policy process has made them silent in numerous cases of international law violations committed by Israel. United States’ concern and alignment towards the Middle East and Eastern European regional hegemon has also played an important piece in their vocal criticisms of Russia’s international norms violations and their normative response towards Israel’s norms breaches.